Using Teaching Aids to Improve Student Learning Outcomes in Islamic Education Learning at MA Negeri 1 Gresik: A Classroom Action Research - Jumhuri, Muhammad Yusuf; Mustakim (Jurnal Profesi Guru Indonesia, 2025)
This study aims to determine the use of teaching aids in improving student learning outcomes at MA Negeri 1 Gresik. This study used an experimental method, involving two groups of students: an experimental group that used teaching aids in their lessons, and a control group that received traditional instruction. The results showed a significant increase in the academic performance of students in the experimental group compared to the control group. The use of teaching aids, such as multimedia presentations, visual materials, and interactive activities, helped students better understand and remember complex concepts. In addition, students in the experimental group showed increased engagement, motivation, and participation in class. These findings suggest that teaching aids can enhance the learning process by making lessons more interactive, accessible, and enjoyable. Based on these results, this study recommends the incorporation of teaching aids into classroom instruction to improve student learning outcomes and foster a more dynamic learning environment.